Analisis Pengelolaan RPH Kota Pamekasan Ditinjau dari Keputusan Kepala Badan BPJPH No. 77 Tahun 2023 - Naurah Intan Fahrani; Muhammad Ersya Faraby (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This study discusses how the management of RPH in Pamekasan City is based on the decision of the Head of BPJPH Agency Number 77 of 2023. This is one of the reasons researchers are interested in researching more deeply into the management of RPH based on the Decree of the Head of BPJPH concerning Halal Slaughter Certification Standards. This research method uses qualitative with the research subject being the Pamekasan City RPH. The data used in this study are primary and secondary data through interviews, observations, and documentation. This research is located at the Pamekasan City RPH. The results of this study state that the Management of RPH has implemented the Decree of the Head of BPJPH Agency Number 77 of 2023 which explains the implementation of a halal product guarantee system in the slaughter of ruminant animals and poultry, starting from location provisions, slaughter tools, pre-slaughter, slaughter process, to distribution of slaughter results. However, there are several indicators that have not been implemented such as stunning, NKV, and locations that are still not feasible.